1996
DOI: 10.1016/0005-2736(95)00263-4
|View full text |Cite
|
Sign up to set email alerts
|

Endocytosis inhibitors abolish the active transport of polypeptides in the mucosa of the nasal upper concha of the rabbit

Abstract: An active absorption of polypeptides (elcatonin = CCT; adrenocorticotropic hormone) had been previously observed in the nasal respiratory mucosa of the rabbit. Its saturation kinetics and the parallel absence of a net transfer of other non-polypeptidic organic markers excluded the involvement of a simple pinocytosis. This absorption has been now better localized and further characterized. Unidirectional CCT fluxes (determined with radioimmunoassay) have been concomitantly monitored with transepithelial electri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 22 publications
0
9
0
1
Order By: Relevance
“…Previous studies have indicated the contribution of specific active transport processes in the absorption of peptides across nasal mucosa. Indeed, the transport of insulin, [1,7 Asu] eel-calcitonin, and ACTH have been proposed to occur through transepithelial receptor-mediated transcytosis processes across nasal epithelium (Cremaschi et al 1991(Cremaschi et al , 1996(Cremaschi et al , 1998(Cremaschi et al , 2001. Furthermore, a non-specific endocytosis has been shown for the permeation of human calcitonin across excised bovine nasal tissue .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have indicated the contribution of specific active transport processes in the absorption of peptides across nasal mucosa. Indeed, the transport of insulin, [1,7 Asu] eel-calcitonin, and ACTH have been proposed to occur through transepithelial receptor-mediated transcytosis processes across nasal epithelium (Cremaschi et al 1991(Cremaschi et al , 1996(Cremaschi et al , 1998(Cremaschi et al , 2001. Furthermore, a non-specific endocytosis has been shown for the permeation of human calcitonin across excised bovine nasal tissue .…”
Section: Discussionmentioning
confidence: 99%
“…The histology, viability, transepithelial electrical resistance (TEER) and aminopeptidase activity of the bovine nasal mucosa make it a suitable model to study the absorption of therapeutically relevant peptides (Schmidt et al , 2000. Previous studies have indicated that different regions of the nasal tissue may be involved in the active absorption of peptide drugs (Cremaschi et al 1991(Cremaschi et al , 1996. Also, by identifying regions with high permeability or specialized transport processes, it was hypothesized that drugs can be targeted and their systemic delivery enhanced (Chien & Chang 1987;Vidgren & Kublik 1998).…”
Section: Introductionmentioning
confidence: 99%
“…PHZ, a specific inhibitor of the Na + /glucose cotransporter (SGLT 1),17,18 was added to the mucosal side. Cytochalasin B, an endocytosis inhibitor,19,20 was dissolved in ethanol due to its hydrophobicity. An aliquot of 25 μL of this ethanol solution was added to each side 5 min prior to the addition of Sit‐G NP, as it was reported that the addition of cytochalasin B to the basolateral side did not affect endocytosis 21 .…”
Section: Methodsmentioning
confidence: 99%
“…These observations suggest an uptake of the chimera into acidic endosomes, as GFP is quenched under acidic conditions. To test this, monensin (5 M) was used to block the pH differential in endosomes (24). There was no loss of P2X 1 -GFP fluorescence on exposure to ␣,␤ϪmeATP (10 M) in the presence of monensin (Figs.…”
Section: Properties Of the Currents Generated By Purinergic Agonists mentioning
confidence: 98%